Serum 25 hydroxyvitamin D concentrations in individuals over 80 years old and their correlations with musculoskeletal and health parameters - Foroni, Mariana Zuccolotto; Cendoroglo, Maysa Seabra; Sakane, Eliane Naomi; Marin-Mio, Rosangela Villa; Moreira, Patricia Ferreira do Prado; Maeda, Sergio Setsuo; Lazaretti-Castro, Marise (Endocrine, 2023)
Purpose The present study aims to evaluate the serum concentrations of 25 hydroxyvitamin D[25(OH)D] in individuals aged ≥80 years, independent, free-living in Sao Paulo, Brazil (Lat 23.5 o S), and to investigate their associations with musculoskeletal system, physical performance and health markers. Method This cross-sectional study included 212 community dwellers aged ≥80 years and evaluated serum 25(OH)D, PTH, calcium, albumin, phosphorus, creatinine, bone markers, and bone mineral density. Physical performance was evaluated with stationary march, Flamingo, and functional reach tests, questionnaires to assess falls and fractures in the previous year, energy expenditure (MET), and Charlson index. Physical activity was evaluated with the International Physical Activity Questionnaire. Results Vitamin D deficiency (<20 ng/mL) was observed in 56% and severe vitamin D deficiency (<10 ng/mL) in 13% of those individuals. Serum concentrations of 25(OH)D were significantly and positively associated with BMD total hip ( p = 0.001), femoral neck ( p = 0.011) and 33% radius ( p = 0.046) BMDs, MET ( p = 0.03) and functional reach test ( p = 0.037) and negatively with age ( p = 0.021), PTH ( p = 0.004) and osteoporosis diagnosis ( p = 0.012). Long-lived individuals with 25(OH)D ≥ 20 ng/mL had higher total hip and femoral neck BMDs ( p = 0.012 and p = 0.014, respectively) and lower PTH ( p = 0.030). In multiple linear regression analysis, age and osteoporosis diagnosis remained negatively associated with 25(OH)D levels ( p = 0.021 and p = 0.001, respectively), while corrected calcium and cholecalciferol use remained positively associated ( p = 0.001 and p = 0.024, respectively). Conclusion We observed high vitamin D inadequacy prevalence in those Brazilian community dwellers’ oldest old. Serum concentrations of 25(OH)D were positively associated with bone mass and dynamic balance, and negatively with PTH and osteoporosis diagnosis. Additionally, 25(OH)D ≥ 20 ng/mL was associated with better bone mass and lower PTH levels.